SGLT2 Inhibitors: From Molecular Mechanisms to Clinical Outcomes in Cardiology and Diabetology - Stielow, Marlena; Fijałkowski, Łukasz; Alaburda, Aidas; Grześk, Grzegorz; Grześk, Elżbieta; Nowaczyk, Jacek; Nowaczyk, Alicja (Molecules (Basel, Switzerland), 2025)
Studies have shown that sodium-glucose cotransporter type 2 (SGLT2) inhibitors not only help lower blood glucose levels but also offer cardioprotective effects, reduce the progression of heart failure, and may even slow the progression of aortic stenosis. The mechanisms of these beneficial properties are thought to involve multiple pathways, including reducing inflammation, oxidative stress, and improving cellular energy metabolism. Advancing knowledge about the mechanisms of action of these drugs and their effects on the course of the aforementioned diseases has become the subject of intensive clinical and scientific research. This publication aims to provide insight into the role of SGLT2 inhibitors in the context of diabetes mellitus, heart failure and acute coronary syndrome, through clinical analysis, mechanistic insights and comparison of the effects of these drugs.